The Effect of the Dose of Ecoenzyme on the Increase in Leaf Area of Kangkung Darat (Ipomoea reptans Poir) - Yosefin Nisa Aulia; Leilani Eka Putri; Azwir Anhar; Violita Violita (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Ecoenzyme is a processed product from organic waste, water and sugar. Ecoenzyme can be a multifunctional liquid, especially in supporting plant growth. The nutrient content contained in ecoenzyme can encourage vegetative plants including the formation of chlorophyll in leaves. To support growth, various doses of ecoeznyme were given to land kale (Ipomoea reptans Poir). This study aims to determine the effect of the dose of ecoenzyme on the increase in leaf area of ​​land kangkung. This research was carried out from January 2022-February 2022 in the Plant Physiology Laboratory and Biology wire house of FMIPA UNP. This study used a completely randomized design (CRD) with 7 treatments and 4 replications. Consists of: P1 (control), P2 (0.5% ecoenzyme), P3 (1% ecoenzyme), P4 (1.5% ecoenzyme), P5 (2% ecoenzyme), P6 (2.5 ecoenzyme), P7 ( 0.3 POC). The data obtained were analyzed by variance (ANOVA) with DMRT further test. The results showed that the dose of ecoenzyme did not have a significant effect on the increase in leaf area of ​​land kangkung (Ipomoea reptans Poir).